Influence of the operating conditions and kinetic analysis of the selective hydrogenation of methyl oleate on Ru–Sn–B/Al2O3 catalysts - Sánchez, María Amparo (2012)
The influence of the operating conditions and preparation methods of Ru–Sn–B/Al2O3 catalysts on the activity and selectivity for the hydrogenation of methyl oleate to oleyl alcohol was studied. It was found that catalysts prepared by incipient wetness (IW) are more active and selective than those prepared by co-impregnation. This better performance is possibly due to a lower level of residual chlorine. The experiences of hydrogenation of methyl oleate showed that activity increases as the reaction temperature increases while the selectivity to oleyl alcohol has a maximum value. This could be due to the higher activation energies for the hydrogenolysis of carboxymethyl groups than those found for C=C double bonds hydrogenation. The increase in operating pressure has a positive effect on the activity but it influences selectivity time patterns in a more complex way. Experiments carried out by varying methyl oleate/n-dodecane ratio show that the selectivity and conversion not depend on this parameter. A simple kinetic model is proposed.